Legalisera, kriminalisera eller acceptera? - En kvalitativ uppsats om de professionellas förhållningssätt och hur de arbetar med cannabisrelaterade problem - Hansson,Philip (2014)
The aim of this study was to examine the effects of the liberalization wave which is sweeping across America in recent times, and how it influence our way of thinking and working with marijuana in Skåne, Sweden. To understand how it’s affecting us my study are based on interviewing social workers and other professionals working with marijuana and other narcotic related problems. My interviews were focused on how the legalization in Colorado, USA and the closeness to Danmark has been affecting our views on the topic in Skåne, both as professionals and their opinion about the clients they meet. We’ve discussed the geographical closeness between Skåne and Christiania in Denmark, and how their policies are affecting us in Skåne, Sweden. The analyses were based on two different kinds of perspectives, one focusing on a larger scale with acculturation and structural functionalism. The other are focused on the individual with the help of a labeling theory. As a conclusion of the first the perspective, I would say that some groups in Sweden have been more affected than others. As for the other more individual perspective one must make the difference between recreational users and problematic users, and the addiction that may follow.
Keywords: marijuana; legalization; liberalization; drug policies; acculturation